How creating one additional well can generate Bose-Einstein condensation - Mihály Máté (Nature Portfolio, 2021)
Bose-Einstein condensation was theoretically predicted almost 150 years ago but experimentally realized this century, reviving the interest in this striking quantum phenomenon. The authors present a system of strongly interacting bosons that have the ability to go from the quasi-condensation state of matter to a fully Bose-Einstein condensate, showing that this phase transition can be achieved by just tuning one parameter.